Availability of sharing services in Szczecin - Stoeck, Tomasz (Przegląd Komunikacyjny)
The article presents the problem of implementation sharing economy services in relation to the urban transport system. Basic information related to this concept and the principle of its operation was discussed, with particular emphasis on economic, ecological and social aspects. The analysis considered the growing role of unmanned rental shops of various types, whose development and functioning influences the change in communication preferences of Szczecin residents. The research part compares travel times of available vehicles on a selected test section. The presented conclusions and observations can be helpful in modernizing current or implementing completely new initiatives in the field of providing modern means of transport. They are to guarantee public availability in a precisely defined area and a relatively short time of use, and at the same time be adapted to the needs of a given agglomeration. Keywords: Sharing services; Urban transport; Communication preferences